Fisika : prinsip dan aplikasi - Douglas C. Giancoli (Erlangga, 2001)
ir, Jil.1=c.1-8; jil.2=c.1-3/oen, jil.2=c.4-5; sn,jl.1,c.9-10,jl.2,c.9; ws.jl.2,c.6-8/tr, jil.1=c.11-13/ir, jil.2,c.10-11/tr, jil.2=c.12-15/irh, jil1,c.14-16